Process of use of evidence products by frontline maternal, newborn and child health staff at the facility level in Ghana - Gordon Abekah-Nkrumah; Doris Ottie-Boakye; Richmond Owusu; Johnson Ermel; Sombié Issiaka; Anita Asiwome Adzo Baku (PLoS ONE, 2025)
Although the use of evidence products has been identified as beneficial in improving reproductive, maternal and child health, very little is known about the processes that facilitate the use of these evidence products by frontline Maternal, Newborn and Child Health and Reproductive and Child Health (RNCH/RCH) practitioners in decision-making on the issues that confront them in their line of work. The study examined the nature, processes, and barriers, to the use of evidence products for care decision-making by frontline MNCH/RCH staff in selected health facilities in Ghana. Using a qualitative case study design, interviews of 24 frontline RNCH/RCH practitioners across 16 healthcare facilities in the Greater Accra, Eastern, and Ashanti regions of Ghana were conducted. The study employed a semi-structured interview guide modelled along the Action Cycle phase of the Knowledge-To-Action (KTA) framework, and the objectives of the study. Themes were built out of the transcribed data. The study revealed that the processes that facilitate the use of evidence products include problem identification activities (such as service evaluation, using accepted benchmarks, inadequate logistics for providing service and client feedback) and, adapting knowledge to their local context. The usual suspects of socio-cultural and health systems-related factors such as resource constraints and human factors were found to hinder the use of evidence products in providing RNCH/RCH services. The study contributes to knowledge by operationalising the KTA, simplifying the concept of knowledge sustainability and makes it easy for adoption and implementation especially at the frontline. Appropriate interventions that rely on strong education to navigate the societal norms and beliefs that inhibit the uptake of evidence-based care by clients will be essential in improving the use of evidence to inform practice decisions.